Experience of burden of care among adult caregivers of elderly persons in Oyo State, Nigeria: a cross-sectional study (2022)
Introduction: caring for elderly persons is challenging for caregivers due to elderly persons´ increased dependence and reduced physical strength. This study assessed the burden of care experienced by caregivers of elderly persons in family settings. Methods: this cross-sectional study used a multistage cluster sampling technique to select 1,119 caregivers of elderly persons aged 18-59 years from one rural and one urban local government area in Oyo State, Nigeria. Interviewer-administered questionnaires collected information on caregiving arrangements and burden of care experienced (determined using the modified short version of the Zarit Burden Interview). Results: caregivers´ mean age was 38.6 ± 8.7 years with 50.2% aged ≥40 years. There were more females (59.8%) than males (40.2%) and 78.4% were married. Only 47.8% were primary caregivers, 54% cared for their parents and 2% cared for non-relatives. Prior to their caregiving, 81% reported good relationships with the elderly. Although 80.3% of the elderly were reported to be fully independent for activities of daily living, 74.0% of the caregivers experienced burden of care with 28.2% reporting severe burden. The odds of burden of care were 10 times higher among rural than urban caregivers (OR=10.09, 95%CI=5.99-17.01); eight times higher among those with poor than those with good mental health status (OR=7.90, 95%CI=4.60-13.57) three times higher among those with dependent than independent elders (OR=2.74, 95%CI=1.68-4.47). Conclusion: experience of burden of care was high among caregivers in the rural area and those with poor mental health. Community-oriented support including daycare centres and old people´s homes will provide relief to caregivers.